Understanding Well-Being in Urban Context: A Survey - Amirhossein Ghaffari; Susanna Pirttikangas; Ekaterina Gilman (IEEE Access)
This survey explores the landscape of well-being research in an urban context with a focus on data. First, we conduct a review of well-being in general and efforts to measure it. Then, we perform an analysis of relevant research papers, reports, surveys, and standards published between January 2018 and September 2023 for the identification of reported factors contributing to urban well-being. These indicators were placed into distinct categories, creating a taxonomy of current efforts toward capturing urban well-being. This taxonomy, presented in a table format, details each indicator alongside its measurement method, data source, and other relevant information. Therefore, we can gain a deeper understanding of how urban well-being is assessed, what the challenges are, the current research focus, and the gaps. Our analysis reveals that urban well-being is a multifaceted construct influenced by a combination of factors. The taxonomy highlights the interconnectedness of these indicators, emphasizing that well-being results from their integration rather than isolated factors. This underscores the complexity of urban life and the need for holistic assessment methods. By providing this taxonomy, we aim to facilitate the development of more holistic approaches to measure and enhance urban well-being. This taxonomy could serve as a valuable tool for practitioners, researchers, and policymakers in the field, providing a comprehensive framework to understand and assess various aspects of capturing well-being in an urban context.